The aesthetic value of the English madrigal - Van Den Borren, Charles (1926)
Bibliotheek Camille Huysmans
Dedicator: Van Den Borren, Charles, dedicatee: Huysmans, Camille
Overdruk uit "Proceedings of the Musical Association", session LII
Engels
Brochure
Keywords: muziekgeschiedenis